Ink composition for seamless printed can, seamless printed coated can and method for manufacturing the same

The ink composition for seamless printing cans, utilizing a combination of carbon blacks with specific particle sizes and acidic carbon black, addresses the challenges of achieving blueness, jet blackness, and corrosion resistance, resulting in stable and high-quality printing.

JP2025051583AActive Publication Date: 2025-04-04TOYO INK MFG CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024063015
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-22
Filing Date
2024-04-09
Publication Date
2025-04-04
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

Existing ink compositions for seamless printing cans struggle to achieve excellent blueness, jet blackness, and pitting corrosion resistance, while also ensuring machine stability and high-speed printing suitability.

Method used

The development of an ink composition for seamless printing cans that uses a combination of carbon blacks with different particle sizes, specifically carbon black (CBI) with an average primary particle diameter of 15 nm to less than 35 nm and carbon black (CBII) with an average primary particle diameter of 35 nm to 60 nm, along with acidic carbon black containing acidic functional groups, to achieve the desired color and corrosion resistance.

Benefits of technology

The ink composition achieves excellent jet blackness, blueness, and high-speed printing suitability, while also providing excellent pitting corrosion resistance on aluminum cans, ensuring machine stability and high-quality printing results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051583000001
    Figure 2025051583000001
  • Figure 2025051583000002
    Figure 2025051583000002
  • Figure 2025051583000003
    Figure 2025051583000003
Patent Text Reader

Abstract

To provide an ink composition for a seamless printed can which has a bluish color tone that is difficult to be expressed in conventional seamless can printing, is excellent in jet-blackness and pitting corrosion resistance, and is also excellent in stability on a machine and high speed printability, and a seamless printed coated can using the same.SOLUTION: An ink composition for a seamless printed can contains a carbon black, a resin and a solvent, wherein the carbon black contains a carbon black (CBI) having an average primary particle diameter of 15 nm or more and less than 35 nm and a carbon black (CBII) having an average primary particle diameter of 35 nm or more and 60 nm or less, and a mass ratio of the CBI to the CBII is 40 / 60 to 95 / 5.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a black ink composition for seamless printed cans and a seamless can printed and coated using the same. In particular, the present invention relates to an ink composition for seamless printed cans that imparts excellent bluish and jet black properties to a printed and coated seamless can and a seamless can printed and coated using the same. [Background technology]

[0002] Metal containers are used for a wide range of applications, including beverage containers, general-purpose cans, candy cans, etc. Metal beverage containers in particular have superior storage stability for the contents compared to plastic beverage containers, and are therefore used for alcoholic beverages, carbonated beverages, soft drinks, coffee beverages, etc.

[0003] Metal beverage containers are mainly manufactured by two methods. One is a method in which a sheet metal plate is printed and painted, and then cut, welded, and other processes are carried out to produce the desired can body. The other is a method in which a metal plate is punched, ironed, and other processes are carried out to form a cylindrical shape with a bottom, and the body of the can is then printed and painted. The latter method is specifically called a seamless can.

[0004] Commonly used seamless cans are steel cans, which are primarily made of iron, and aluminum cans, which are primarily made of aluminum. To display designs or content on these seamless cans, there are several methods, such as printing directly onto the container or attaching a printed film to the container.

[0005] Patent Document 1 describes an ink composition for metal printing that contains carbon black. Among seamless printing can inks used when directly printing on containers, black inks used on beverage containers for black coffee, etc., are required to have a high level of jet blackness. Furthermore, in recent years, there has been an increasing demand for black inks with a bluish hue rather than black inks with a reddish or brownish hue.

[0006] In addition, black inks used on aluminum cans are also required to be resistant to pitting corrosion, which is a corrosion phenomenon in which the surface of the printed coating becomes rough or holes appear in the printed and painted aluminum can due to the action of foreign matter adhering to the surface of the aluminum can. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 7284896 Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention aims to provide an ink for seamless printing on cans, which has a bluish hue that has been difficult to achieve in the past, is excellent in jet blackness and pitting corrosion resistance, and is also excellent in on-press stability and suitability for high-speed printing.

[0009] In order to solve the above problems, the present invention has developed a black ink for seamless printing cans that has excellent jet blackness and a bluish tint by combining carbon blacks with different particle sizes. In addition, it has been discovered that by including a specific ratio of acidic carbon black, which has acidic functional groups introduced on the surface, in the total carbon black, the ink also has excellent pitting corrosion resistance on aluminum cans, leading to the completion of the present invention.

[0010] That is, the present invention relates to an ink composition for seamless printed cans, which contains carbon black, a resin, and a solvent, wherein the carbon black contains carbon black (CBI) having an average primary particle diameter of 15 nm or more and less than 35 nm, and carbon black (CBII) having an average primary particle diameter of 35 nm or more and 60 nm or less, and the mass ratio of CBI to CBII is 40 / 60 to 95 / 5.

[0011] Furthermore, the present invention relates to the ink composition for seamless printed cans, wherein the content of acidic carbon black in the carbon black is 80 mass % or more.

[0012] Furthermore, the present invention relates to the ink composition for seamless printed cans, wherein the difference in average primary particle size between CBI and CBII is 5 nm or more.

[0013] Furthermore, the present invention relates to the ink composition for seamless printed cans, wherein the content of carbon black in the ink composition is 20 to 45 mass %.

[0014] The present invention further relates to a printed and coated seamless can having a printed layer made of the ink composition for seamless printed cans provided on a metal printing medium, and an overprint layer made of an overprint varnish provided on the printed layer.

[0015] Furthermore, the present invention relates to a method for producing printed and coated seamless cans, which comprises dry offset printing or offset printing the ink composition for seamless printed cans on a metal printing medium to form a printed layer, and applying an overprint varnish onto the printed layer to form an overprint layer. Effect of the Invention

[0016] According to the present invention described above, it is possible to provide an ink composition for seamless printed cans which has a bluish tint and is excellent in jet blackness, on-press stability and suitability for high-speed printing, and a printed article obtained by printing the ink composition, and it is also possible to provide a printed article which exhibits good pitting corrosion resistance on seamless cans made of aluminum material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The carbon black used in the present invention may be any of various carbon blacks, such as furnace black, channel black, thermal black, and acetylene black, which are produced by various production facilities.

[0018] The carbon black in the ink composition of the present invention is a combination of carbon black (CBI) having an average primary particle diameter of 15 nm or more and less than 35 nm and carbon black (CBII) having an average primary particle diameter of 35 nm or more and 60 nm or less. Carbon black having an average primary particle diameter of 15 nm or more and less than 35 nm is easy to obtain an ink with high jet blackness, and carbon black having an average primary particle diameter of 20 nm or more and 30 nm or less is more preferable. Carbon black having an average primary particle diameter of 35 nm or more and 60 nm or less is easy to obtain an ink with a bluish hue, and carbon black having an average primary particle diameter of 40 nm or more and 50 nm or less is more preferable. By using these in combination, an ink composition for seamless printing cans excellent in jet blackness, bluishness, and high-speed printability can be obtained.

[0019] Here, the average primary particle size refers to a value measured by electron microscopy. For example, the maximum particle sizes of approximately 2,000 to 3,000 randomly selected pigment particles are measured using a field emission scanning electron microscope (JSM-7000F manufactured by JEOL Ltd.) and the average value is taken as the average primary particle size. When the average primary particle size of carbon black is expressed as a frequency distribution, commercially available carbon black generally exhibits a symmetrical mountain shape with the average primary particle size as a peak. The distribution curve expressing the average primary particle size of carbon black in the ink composition of the present invention as a frequency distribution exhibits an asymmetrical mountain shape or a mountain shape with two or more peaks.

[0020] The difference in average primary particle size between CBI and CBII is preferably 3 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more, because this provides better jet blackness, blueness, suitability for high-speed printing, and the like.

[0021] In addition, the nitrogen adsorption specific surface area of ​​CBI is 75 to 350 m 2 / g, and 90 to 180m 2 / g is more preferable. The nitrogen adsorption specific surface area of ​​CBII is 30 to 70 m 2 / g, and 35 to 60m 2 / g is more preferable. By using carbon black in these ranges in combination, a composition for seamless printed cans that is excellent in jet blackness, blueness, and high-speed printability can be obtained. The nitrogen adsorption specific surface areas are all defined in accordance with JIS K 6217.

[0022] CBIs include MA77 (23 nm), MA7 (24 nm), MA8 (24 nm), MA11 (29 nm) manufactured by Mitsubishi Chemical Corporation, Special Black 5 (20 nm), Special Black 4 (25 nm), Special Black 4A (25 nm) manufactured by Orion Engineered Carbons Co., Ltd., and can be used alone or in combination of two or more. CBIIs include MOGUL-E (48 nm) manufactured by CABOT Corporation, MA14 (40 nm), MA285 (40 nm), MA220 (55 nm) manufactured by Mitsubishi Chemical Corporation, and can be used alone or in combination of two or more.

[0023] The ratio of the carbon blacks used in combination is preferably a mass ratio of CBI to CBII in the range of 40 / 60 to 95 / 5, more preferably in the range of 50 / 50 to 93 / 7, and even more preferably in the range of 60 / 40 to 90 / 10. When the mass ratio is within the above range, an ink composition for seamless printing cans having excellent bluish and jet black properties and high-speed printability can be easily obtained.

[0024] The carbon black in the ink composition of the present invention preferably contains 80% by mass or more of acidic carbon black having an acidic functional group introduced therein. More preferably, it is 85% or more, and even more preferably, it is 90% or more. The pH of the acidic carbon black is in the range of 2.0 to 6.0, and preferably in the range of 2.5 to 5.0. The pH here is a value measured by a glass electrode pH meter for a mixture of carbon black and distilled water. By using acidic carbon black within the above range, the ink composition exhibits good pitting corrosion resistance even when the substrate is an aluminum container that is not size-coated or coated. It is considered that the oxygen on the surface of the carbon black is less likely to receive electrons released from the aluminum, and as a result, corrosion due to galvanic action is less likely to progress. However, the above is based on scientific considerations, and the present invention is not limited to this action alone. Examples of the acidic functional group include a carboxyl group and a phenolic hydroxyl group.

[0025] The carbon black content in the ink composition of the present invention is in the range of 20 to 45% by mass, more preferably 25 to 40% by mass. By having the carbon black content in the above range, the ink composition for seamless printed cans has excellent dispersion stability, and excellent coating properties, jet blackness, and pitting corrosion resistance.

[0026] As the solvent used in the ink composition for seamless printed cans of the present invention, a solvent suitable for printing inks such as a high boiling point petroleum solvent, an aliphatic hydrocarbon solvent, a higher alcohol solvent, etc. can be used, and the use of a high boiling point petroleum solvent is particularly preferred. The above solvents can be used alone or in combination of two or more kinds.

[0027] High-boiling petroleum solvents are mainly composed of naphthenic or isoparaffinic solvents, and non-aromatic solvents that do not contain aromatic compounds are preferable in consideration of the environmental impact. Non-aromatic solvents among high-boiling petroleum solvents include AF Solvent No. 4 to No. 7 manufactured by Nippon Oil Corporation and Exxon Mobil Corp.'s Exxol D110 and D130. Some higher alcohol solvents may also be used in combination.

[0028] In addition to petroleum-based solvents, fatty acid esters and the like can also be used.

[0029] The content of the solvent is not particularly limited. For example, the content of the solvent in the ink composition for seamless printed cans is preferably 10% by mass or more, more preferably 15% by mass or more. The content of the solvent in the ink composition for seamless printed cans is preferably 60% by mass or less, more preferably 50% by mass or less. By having the content of the solvent within the above range, the ink composition for seamless printed cans can be easily adjusted to an ink tack value that shows good printability on seamless cans that are printed in large quantities at high speed.

[0030] The resin used in the ink composition of the present invention is preferably a fatty acid-modified alkyd resin. Since the fatty acid-modified alkyd resin has a high affinity for the particle surface of carbon black, it is easy to obtain an ink for seamless printing cans that has a bluish hue, excellent jet blackness, and excellent pitting corrosion resistance. The fatty acid-modified alkyd resin is obtained by condensation of a polybasic acid, a polyhydric alcohol, and a fatty acid component.

[0031] The fatty acid component is not particularly limited as long as it is a fatty acid or oil having an iodine value of 100 or less, and examples thereof include coconut oil fatty acid, palm oil fatty acid, palm kernel oil fatty acid, olive oil, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, etc. From the viewpoint of jet-black color, it is preferable to include a fatty acid or oil having a hydroxyl group as the fatty acid component. Examples include 12-hydroxystearic acid, ricinoleic acid, castor oil fatty acid, hydrogenated castor oil fatty acid, castor oil, hydrogenated castor oil, etc. These are classified as non-drying oils, and are unlikely to produce a specific odor due to components derived from fatty acids, and therefore the flavor of the contents of the seamless can is unlikely to be impaired.

[0032] Examples of polybasic acids constituting the fatty acid modified alkyd resin include dibasic acids such as phthalic acid, phthalic anhydride, isophthalic acid, terephthalic acid, succinic anhydride, adipic acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and maleic anhydride, and tribasic acids such as trimellitic anhydride and methylcyclohexene tricarboxylic anhydride. Polybasic acids may be used in combination.

[0033] Examples of polyhydric alcohols that can be used to compose the fatty acid-modified alkyd resin include dihydric alcohols such as ethylene glycol, diethylene glycol, triethylene glycol, 1,6-hexanediol, bisphenol A, and hydrogenated bisphenol A; trihydric alcohols such as glycerin, trimethylolethane, trimethylolpropane, and tris(2-hydroxyethyl)isocyanurate; and tetrahydric or higher alcohols such as pentaerythritol and dipentaerythritol. Polyhydric alcohols may be used in combination.

[0034] The method for producing the fatty acid-modified alkyd resin is not particularly limited. For example, it can be produced by known methods such as the transesterification method using oil as a raw material and the fatty acid method using fatty acid as a raw material. For example, the above-mentioned fatty acid, polybasic acid, and polyhydric alcohol are charged together with xylene in a reaction vessel equipped with a stirrer, a reflux condenser, and a thermometer, and the temperature is raised to 240°C while stirring in a nitrogen atmosphere to carry out the esterification reaction. Then, the reaction is terminated after confirming that the acid value is at an arbitrary value, thereby obtaining a fatty acid-modified alkyd resin, which is a condensation polymer of a polybasic acid, a polyhydric alcohol, and a fatty acid component.

[0035] The fatty acid-modified alkyd resin preferably has a styrene-equivalent weight average molecular weight of 3,000 to 30,000. When the weight average molecular weight of the fatty acid-modified alkyd resin is within the above range, the ink composition for seamless printed cans maintains the coating film properties and suppresses misting in terms of printability, which is preferable. In this embodiment, the weight average molecular weight is a value measured by gel permeation chromatography (GPC).

[0036] In addition to the fatty acid-modified alkyd resin, the resin of this embodiment may be a conventionally used resin for ink. That is, the ink composition for seamless printed cans may use a known resin that is compatible with the fatty acid-modified alkyd resin depending on the required performance such as printability and coating film properties. Examples of such resins include oil-free polyester resins, petroleum resins, epoxy resins, ketone resins, rosin-modified phenolic resins, rosin-modified maleic acid resins, melamine resins, and benzoguanamine resins in addition to the fatty acid-modified alkyd resins described above.

[0037] The resin content is not particularly limited as long as it can be adjusted to a predetermined ink tack value. For example, the resin content in the ink composition for seamless printed cans is preferably 20% by mass or more, more preferably 30% by mass or more. The resin content in the ink composition for seamless printed cans is preferably 60% by mass or less, more preferably 50% by mass or less. By having the resin content in the above range, the ink composition for seamless printed cans maintains performance in terms of printability, such as transferability and misting, and is also excellent in coating film properties.

[0038] In addition to the above components, the ink composition for seamless printed cans of this embodiment may contain optional additives that are usually added to ink compositions for seamless printed cans. The optional components include pigment dispersants, driers, lubricants, viscosity modifiers, storage stabilizers, etc. Furthermore, inorganic pigments and organic pigments may be used as necessary.

[0039] The method for preparing the ink composition for seamless printed cans of the present embodiment is not particularly limited. For example, the ink composition for seamless printed cans can be prepared by a conventional method using a three-roll mill, a ball mill, a bead mill, or the like.

[0040] The viscosity of the ink composition for seamless printed cans of this embodiment is not particularly limited, but is from 5 Pa·s to 30 Pa·s, and preferably from 7 Pa·s to 20 Pa·s. The viscosity was measured using a viscoelasticity measuring device (Discovery HR-2, manufactured by TA Instruments Japan) at a temperature of 30°C and a shear rate of 100 sec -1 This is the measured value at .

[0041] The printing method for the ink composition for seamless printed cans of the present invention is not particularly limited, and may be appropriately selected from methods such as a dry offset method using a resin relief plate used in printing on printed and coated seamless cans, and an offset method using a waterless planographic plate.

[0042] The printed and coated seamless can of this embodiment has a printed layer made of an ink composition for seamless printed cans provided on a metal printing medium, and an overprint layer made of an overprint varnish provided on the printed layer.

[0043] Metal printing media on which the ink composition for seamless printed cans of the present invention is printed include, but are not limited to, aluminum plates, steel plates, and coated plates obtained by laminating these with polyester films, etc. These substrates may be subjected to chemical conversion treatment, plating treatment, size coating, white coating, silver coating, etc.

[0044] The step of providing a printing layer is preferably one of a dry offset method using a resin letterpress and an offset method using a waterless planographic plate. By using these printing plates, clear characters and images can be formed on the curved surface of a printed and coated seamless can printed with the ink for seamless printed cans of the present invention, even at high speeds of over one thousand and several hundred cans per minute.

[0045] The thickness of the printed layer is not particularly limited. For example, the thickness of the printed layer is preferably 0.3 μm or more, and more preferably 0.4 μm or more. The thickness of the printed layer is preferably 6.0 μm or less, and more preferably 4.0 μm or less. When the thickness of the printed layer is within the above range, the method for producing seamless printed cans can prevent problems in the can-making process.

[0046] The process of providing the overprint layer is not particularly limited, but it is preferable to apply the overprint layer by a wet-on-wet method in which the overprint layer is formed without curing the printed layer, and then the coating film is cured.

[0047] The overprint varnish is not particularly limited and any known varnish can be used. Examples include thermosetting overprint varnishes such as polyester-melamine, polyester-epoxy-melamine, and polyester-acrylic-melamine varnishes that are usually used for seamless printing cans. In addition, the varnish may be either water-based or solvent-based.

[0048] The thickness of the coating film including the print layer and the overprint layer is not particularly limited. For example, the coating film thickness is preferably 3.0 μm or more, more preferably 6.0 μm or more. The coating film thickness is preferably 30.0 μm or less, more preferably 20.0 μm or less. When the coating film thickness is within the above range, the resulting print-coated seamless can has excellent appearance such as gloss, and the coating film having excellent coating film properties for protecting the ink layer is easily obtained.

[0049] The baking conditions in the step of baking and hardening the coating film are not particularly limited. For example, the baking conditions are a first baking at a temperature of 180°C to 300°C for about 3 to 90 seconds, and a second baking at a temperature of 180°C to 300°C for about 30 to 150 seconds for heat hardening. However, depending on the type of can, baking may be performed once. In this way, a printed and painted seamless can consisting of a multi-layer coating film is manufactured.

[0050] The printed and coated seamless cans and test panels of the present invention are * a * b * L in the color space (CIE1976) * and b * The evaluation is based on the value obtained by measuring L. * a * b * In the color system, lightness is L * , hue a * and b * It is expressed as:

[0051] L * The larger the value, the brighter the color, and the smaller the value, the darker the color. * The smaller the value, the better the jet blackness. The black ink composition was transferred to a metal printing medium with a film thickness of 2 μm, and then an overprint varnish was applied and baked to harden the printed matter. * The value is preferably 15.0 or less, more preferably 10.0 or less.

[0052] a * and b * The value of indicates the color direction, and * (+) is a red hue * (-) represents a green hue, and b * (+) is a yellowish hue. * (-) indicates a blue hue. * The smaller the value, the more bluish the ink is. The black ink composition was transferred to a metal printing medium with a film thickness of 2 μm, and then an overprint varnish was applied and baked to harden the printed matter. * A value of 2.0 or less is preferred, and 1.5 or less is more preferred. EXAMPLES

[0053] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited thereto. The numbers in the tables below are based on mass.

[0054] An ink composition for seamless printing cans was prepared according to the following formulation.

[0055] <Synthesis of fatty acid modified alkyd resin> 10.5 parts of 12-hydroxystearic acid, 24.5 parts of coconut oil fatty acid, 35.6 parts of phthalic anhydride, 18.2 parts of pentaerythritol, and 18.2 parts of trimethylolpropane were esterified in a conventional manner to obtain a fatty acid-modified alkyd resin with a fatty acid content of 35%, an acid value of 4.3 mgKOH / g, and a weight average molecular weight of 7,800. The dehydration amount was 7.0%. In Examples 1 to 30 and Comparative Examples 1 to 5, the above fatty acid-modified alkyd resin was used.

[0056] <Preparation of printing ink composition> Using the obtained fatty acid modified alkyd resin, inks for seamless printing cans of Examples and Comparative Examples were prepared in the formulations shown in Tables 1 and 2. The carbon black used was as follows, and the solvent was Linear Alkyl Benzene manufactured by Nippon Oil Corporation, and the additive was Solsperse 20000 manufactured by Lubrizol Japan, Ltd.

[0057] CB(A): MA77 manufactured by Mitsubishi Chemical Corporation (average primary particle diameter 23 nm, specific surface area 130 m 2 / g, pH 2.5) CB(B): MOGUL-E manufactured by CABOT Corporation (average primary particle diameter 48 nm, specific surface area 57 m 2 / g, pH 2.5) CB(C): Mitsubishi Chemical Corporation #47 (average primary particle size 23 nm, specific surface area 132 m 2 / g, pH 7.5) CB(D): REGAL350R manufactured by CABOT Corporation (average primary particle diameter 48 nm, specific surface area 58 m 2 / g, pH 7.0) CB(E): MA11 manufactured by Mitsubishi Chemical Corporation (average primary particle diameter 29 nm, specific surface area 92 m 2 / g, pH 2.5) CB(F): MA14 manufactured by Mitsubishi Chemical Corporation (average primary particle diameter 40 nm, specific surface area 56 m 2 / g, pH 3.0) CB(A), CB(B), CB(E), and CB(F) are acidic carbon blacks whose surfaces have been treated with an acid, and CB(C) and CB(D) are neutral carbon blacks whose surfaces have not been treated with an acid.

[0058] TV in the table indicates the tack value of the ink, and is the value measured using a digital incometer (manufactured by Toyo Seiki Seisakusho Co., Ltd.) with 1.31cc of ink, a room temperature of 25°C, a roller temperature of 30°C, and a rotation speed of 400 rpm for 1 minute. FV indicates the flow value of the ink, and is the diameter value (unit: mm) of the spread after 60 seconds at a room temperature of 25°C using a parallel plate viscometer (spread meter) (manufactured by Yasuda Seiki Seisakusho Co., Ltd.).

[0059] For the printing inks prepared in Examples 1 to 30 and Comparative Examples 1 to 5, test panels were prepared by the following method, and the jet-blackness, hue, and pitting corrosion resistance were evaluated using the test panels. In addition, the on-press stability was also evaluated.

[0060] <Jet black> The printing inks prepared in Examples 1 to 30 and Comparative Examples 1 to 5 were uniformly transferred onto a test rubber roll using a high-speed printability tester (PM904PT, manufactured by SMT Corporation) so that the ink film was 2 μm thick on the substrate, and then transferred to an aluminum plate at a printing speed of 8 m / s. Immediately after this, a thermosetting overprint varnish was applied onto the printed ink layer at a speed of 2 m / s so that the film thickness was 13 μm. The printed coating film was then baked at 200° C. for 3 minutes to produce a printed coating film. The printed coating film was measured using a spectrophotometer (manufactured by X-rite), and the L * a * b * L in color space * The evaluation was based on the numerical value of the value. (Evaluation Criteria) A:L * The color measurement result is 10 or less, and the jet black color is excellent. B:L * The color measurement result is greater than 10 and less than 15, and there is no problem with the quality. C:L * The color measurement result is greater than 15, and the jet blackness is significantly inferior, making it unusable as a product. The practical evaluations are A and B.

[0061] <Hue> The printing inks prepared in Examples 1 to 30 and Comparative Examples 1 to 5 were uniformly transferred onto a test rubber roll using a high-speed printability tester (PM904PT, manufactured by SMT Corporation) so that the ink film was 2 μm thick on the substrate, and then transferred to an aluminum plate at a printing speed of 8 m / s. Immediately after this, a thermosetting overprint varnish was applied onto the printed ink layer at a speed of 2 m / s so that the film thickness was 13 μm. The printed coating film was then baked at 200° C. for 3 minutes to produce a printed coating film. The printed coating film was measured using a spectrophotometer (manufactured by X-rite), and the L * a * b * b in color system * The evaluation was based on the numerical value of the value. (Evaluation Criteria) A:b * The color measurement result is 1.5 or less and has a strong bluish tint. B:b * The color measurement result is greater than 1.5 and less than 2.0, and the color has a slight bluish tint. C:b * The color measurement result is greater than 2.0 and has a weak blue tint. The practical evaluations are A and B.

[0062] <Pitting corrosion resistance> The printing inks prepared in Examples 1 to 30 and Comparative Examples 1 to 5 were uniformly transferred to a test rubber roll using an RI tester (manufactured by Kokubo Seimitsu Co., Ltd.) so that the thickness of the ink film on the substrate was 2 μm, and then transferred to an aluminum plate. Then, a thermosetting overprint varnish was applied onto the printed ink layer so that the film thickness was 13 μm. Then, the printed coating film was produced by baking at 200° C. for 3 minutes. The printed and coated plate was immersed in a 1% aqueous solution of sodium chloride at 40° C. for 168 hours. Then, the coated plate was taken out, and cellophane adhesive tape was attached to the printed part, and then the tape was peeled off. It was visually judged whether the ink on the printed part had peeled off (corrosion state). (Evaluation Criteria) A: No peeling of the coating occurs B: There is very little peeling of the coating, but it does not affect the quality. C: Slight peeling of the coating is observed, but does not affect the quality. D: A small amount of paint peeling is observed, and the product cannot be used. E: The paint film has clearly peeled off and the product cannot be used. The practical evaluations are A, B, and C.

[0063] <On-board stability> For the printing inks prepared in Examples 1 to 30 and Comparative Examples 1 to 5, 1.31 cc of ink was evenly placed on the rubber roll of a digital inkometer (manufactured by Toyo Seiki Seisakusho Co., Ltd.), and the time until the tack value reached a maximum was measured under conditions of 40°C and 1200 rpm, to evaluate the on-press stability. Note that the longer the time it takes to reach the maximum value, the more suppressed the release of the solvent from the ink, and the less change in the fluidity and viscosity of the ink on the ink roller or blanket, which can be said to be excellent in on-press stability. (Evaluation Criteria) A: Maximum value after 20 minutes B: Maximum value is reached between 10 and 20 minutes C: Maximum value in less than 10 minutes The practical evaluations are A and B.

[0064] <High-speed printing suitability (inking property)> For the printing inks prepared in Examples 1 to 30 and Comparative Examples 1 to 5, 0.2 cc of ink was supplied to a leveling roll using a high-speed printability tester (PM904PT manufactured by SMT Co., Ltd.), and after uniformization, it was transferred to a test rubber roll, and then transferred to an aluminum plate at a printing speed of 8 m / s. Immediately after that, a thermosetting overprint varnish was applied onto the printing ink layer at a speed of 2 m / s to a film thickness of 13 μm. Then, it was baked at 200° C. for 3 minutes to prepare a printing coating film. (Evaluation Criteria) A: The substrate is sufficiently concealed and the ink adhesion is good. B: Slight loss of ink is observed. C: Somewhat noticeable ink loss is observed. D: There is ink void or the aluminum substrate is not sufficiently concealed, and ink adhesion is poor. The practical evaluations are A, B, and C.

[0065] [Table 1] JPEG2025051583000002.jpg223158

[0066] [Table 2]

[0067] The formulations of the examples and comparative examples are as follows. (I) Table 1 (Examples 1 to 30) The ink composition contains fatty acid modified alkyd resin, carbon black, and a solvent, and the carbon black component contained in the ink composition is (1) Carbon black with an average primary particle size of 15 nm or more and less than 35 nm, and carbon black with an average primary particle size of 35 nm or more and less than 60 nm (2) The mass ratio of carbon black having an average primary particle diameter of 15 nm or more and less than 35 nm to carbon black having an average primary particle diameter of 35 nm or more and less than 60 nm is 40 / 60 to 95 / 5. (II) Table 2 (Comparative Examples 1 to 4) The difference from the compositions of the examples is that it does not contain carbon black having an average primary particle size of 15 nm or more and less than 35 nm, or carbon black having an average primary particle size of 35 nm or more and less than 60 nm. (III) Table 2 (Comparative Example 5) The difference between the compositions of the examples is that the mass ratio of carbon black having an average primary particle diameter of 15 nm or more and less than 35 nm to carbon black having an average primary particle diameter of 35 nm or more and less than 60 nm is not in the range of 40 / 60 to 95 / 5.

[0068] As shown in Tables 1 and 2, when the ink compositions for seamless printed cans described in the examples of the present invention were used, ink compositions for seamless printed cans having high jet blackness, expressing a bluish color, excellent pitting corrosion resistance, and a practical level of on-press stability and excellent suitability for high-speed printing could be obtained, compared to the case where the ink compositions for seamless printed cans of the comparative examples were used.

Claims

1. The ink composition for seamless printed cans contains carbon black, a resin, and a solvent, the carbon black containing carbon black (CBI) having an average primary particle diameter of 15 nm or more and less than 35 nm, and carbon black (CBII) having an average primary particle diameter of 35 nm or more and 60 nm or less, and the mass ratio of CBI to CBII is 40 / 60 to 95 / 5.

2. 2. The ink composition for seamless printed cans according to claim 1, wherein the content of the acidic carbon black in the carbon black is 80 mass % or more.

3. 2. The ink composition for seamless printed cans according to claim 1, wherein the difference in average primary particle size between CBI and CBII is 5 nm or more.

4. 2. The ink composition for seamless printed cans according to claim 1, wherein the content of carbon black in the ink composition is 20 to 45 mass %.

5. 5. A printed and coated seamless can comprising: a printed layer formed on a metal printing medium, the printed layer comprising the ink composition for seamless printed cans according to claim 1; and an overprint layer formed on the printed layer, the overprint layer comprising a varnish for overprinting.

6. A method for producing printed and coated seamless cans, comprising: forming a printed layer on a metal printing medium by dry offset printing or offset printing the ink composition for seamless printed cans according to any one of claims 1 to 4; and applying an overprint varnish onto the printed layer to form an overprint layer.

Citation Information

Patent Citations

  • Nonmagnetic one-component developer and image forming method

    JP1997166890A

  • Colorant composition

    JP2003277518A

  • Printing ink composition for seamless can

    JP2009249435A

  • Printing ink composition

    JP2010047652A

  • Printed seamless can and method of manufacturing the same

    JP2012086870A